Optimal bladder filling during high-dose-rate intracavitary brachytherapy for cervical cancer: a dosimetric study - Mahantshetty, Umesh; Shetty, Saurabha; Majumder, Dipanjan; Adurkar, Pranjal; Swamidas, Jamema; Engineer, Reena; Chopra, Supriya; Shrivastava, Shyamkishore (Journal of Contemporary Brachytherapy, 2017)
Purpose: The aim of this study is to compare 3D dose volume histogram (DVH) parameters of bladder and other organs at risk with different bladder filling protocol during high-dose-rate intracavitary brachytherapy (HDR-ICBT) in cervical cancer, and to find optimized bladder volume. Material and methods : This dosimetric study was completed with 21 patients who underwent HDR-ICBT with computed tomography/magnetic resonance compatible applicator as a routine treatment. Computed tomography planning was done for each patient with bladder emptied (series 1), after 50 ml (series 2), and 100 ml (series 3) bladder filling with a saline infusion through the bladder catheter. Contouring was done on the Eclipse Planning System. 7 Gy to point A was prescribed with the standard loading patterns. Various 3D DVH parameters including 0.1 cc, 1 cc, 2 cc doses and mean doses to the OAR’s were noted. Paired t-test was performed. Results : The mean (± SD) bladder volume was 64.5 (± 25) cc, 116.2 (± 28) cc, and 172.9 (± 29) cc, for series 1, 2, and 3, respectively. The 0.1 cm 3 ,1 cm 3 , 2 cm 3 mean bladder doses for series 1, series 2, and series 3 were 9.28 ± 2.27 Gy, 7.38 ± 1.72 Gy, 6.58 ± 1.58 Gy; 9.39 ± 2.28 Gy, 7.85 ± 1.85 Gy, 7.05 ± 1.59 Gy, and 10.09 ± 2.46 Gy, 8.33 ± 1.75 Gy, 7.6 ± 1.55 Gy, respectively. However, there was a trend towards higher bladder doses in series 3. Similarly, for small bowel dose 0.1 cm 3 , 1 cm 3 , and 2 cm 3 in series 1, 2, and 3 were 5.44 ± 2.2 Gy, 4.41 ± 1.84 Gy, 4 ± 1.69 Gy; 4.57 ± 2.89 Gy, 3.78 ± 2.21 Gy, 3.35 ± 2.02 Gy, and 4.09 ± 2.38 Gy, 3.26 ± 1.8 Gy, 3.05 ± 1.58 Gy. Significant increase in small bowel dose in empty bladder (series 1) compared to full bladder (series 3) (p = 0.03) was noted. However, the rectal and sigmoid doses were not significantly affected with either series. Conclusions : Bladder filling protocol with 50 ml and 100 ml was well tolerated and achieved a reasonably reproducible bladder volume during cervical brachytherapy. In our analysis so far, there is no significant impact of bladder filling on DVH parameters, although larger bladders tend to have higher doses. Small bowel doses are lesser with higher bladder volumes. Further evaluation and validation are necessary.